Technology Integration in Technical and Vocational Education and Training (TVET): The Role of the Art Teacher - Richard, Gbadegbe Selase; Joseph, Amewu; Elikem, Krampa; Edem, Buami Kwami (Journal of Technical Education and Training, 2023)
The quality of teaching and learning across all TVET disciplines can be enhanced by promoting technology-inclusive TVET. Using the Technological Pedagogical and Content Knowledge (TPACK) model, this study examines the interrelationships between the knowledge required by art teachers to effectively integrate technology in teaching at the TVET level. The study assumed that quality TVET practices could be achieved if TVET teachers had a solid understanding of their subject matter, pedagogical procedures and knowledge about employing technological tools. This research used a quantitative data approach and adopted a Structural Equation Modelling (SEM) analysis technique to measure the path coefficients of direct or indirect influence between exogenous and endogenous variables. A quantitative survey instrument based on the TPACK model was adopted to collect data from 152 art teachers sampled across various public educational institutions in Ghana. Data analysis was performed with SPSS and SmartPLS using an online data collection procedure. The study demonstrates a significant relationship between art teachers’ knowledge and how much technology can be integrated with TVET. The following mechanisms were revealed: the mastery of technological tools, technologically driven instructional approaches, and a teacher’s technical knowledge and abilities as the fundamental mechanisms required to foster efficient skill development at the TVET level. This implies that educators, training institutions, policymakers, and stakeholders in the TVET ecosystem should pay special attention to these mechanisms to strengthen the teaching and learning delivery of TVET.